Combination of STING Pathway Agonist With Saponin Is an Effective Adjuvant in Immunosenescent Mice - Vassilieva, Elena V.; Taylor, Dahnide W.; Compans, Richard W. (Frontiers in Immunology, 2019)
There is an urgent need to improve protective responses to influenza vaccination in the elderly population, which is at especially high risk for adverse outcomes from influenza infection. Currently available inactivated vaccines provide limited protection, even when a four-fold higher dose of the vaccine is administered. Adjuvants are often added to vaccines to boost protective efficacy. Here we describe a novel combination of an activator of the STING pathway, 2’3 cyclic guanosine monophosphate–adenosine monophosphate (cGAMP) with a saponin adjuvant, that we found to be highly effective in boosting protective immunity from vaccination in an aged mouse model. Using this combination with a subunit influenza vaccine, we observed that survival of vaccinated 20 month-old mice after lethal challenge increased from 0-20% with unadjuvanted vaccine to 80-100%, depending on the vaccination route. Compared to unadjuvanted vaccine, the levels of vaccine-specific IgG and IgG2a increased by almost two orders of magnitude as early as two weeks after a single immunization with the adjuvanted formulation. By analyzing phosphorylation of interferon regulatory factor 3 (IRF3) in cell culture, we provide evidence that the saponin component increases access of exogenous cGAMP to the intracellular STING pathway. Our findings suggest that combining a STING activator with a saponin-based adjuvant increases the effectiveness of influenza vaccine in aged hosts, without having to increase dose or perform additional vaccinations. This study reports a novel adjuvant combination that a) is more effective than current methods of boosting vaccine efficacy, b) can be used to enhance efficacy of licensed influenza vaccines, and c) results in effective protection using a single vaccine dose.